O Processo Avaliativo no Ensino de Música na Educação Básica: uma proposta para a Educação Infantil e Anos Iniciais do Ensino Fundamental - Melo, Kelli Ivo Barbosa de (2023)
The focus of this research is to investigate music assessment in basic education, specifically in the Art curricular component, in early childhood education and the early years of Elementary School, theme arising from personal concerns in the face of challenges faced in teaching practice, and since then, conceptualized as a relevant and coherent element of an effective musical teaching process. The development of this study centered on answering how to evaluate and which criteria will guide the evaluation process, and for that purpose, the theoretical analysis is based on the authors of the field of Music Education, in particular the Model C(L)A(S)P (Keith Swanwick, 1979), the criteria from the Spiral Theory of Musical Development (Swanwick, 1994) for evaluating musical making, and the methodological design is fragmented into two parts, at first, composed of a bibliographical-documental research, of a qualitative nature, from the perspective of understanding how thematic evaluation in Music Education has been approached. And, causing in the second moment, the proposition of an intervention for the evaluation of the students of the corresponding stages, with the proposal of a didactic sequence for the elaboration of a Portfolio, developed for a constant evaluation process, with the perspective of deepening the vision and improving teaching practice that provides a satisfactory, strengthened and grounded musical learning process. Keywords: Music education. Basic education. Assessment. Spiral theory